Hegemony of Power in the Film “Cairo Conspiracy” by Tarik Saleh (Antonio Gramsci’s Theory of Hegemony) - Naufal Adya Wijaya; Rohanda Rohanda; Ihin Solihin (Hasanuddin University, 2025)
This research analyzes the representation of hegemony of power in Tarik Saleh's 2022 film